2003
DOI: 10.3168/jds.s0022-0302(03)73760-6
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Forage and Solin Supplementation on Conjugated Linoleic Acid Levels in Plasma and Milk

Abstract: Two experiments were run concurrently to determine the effect of fresh forage consumption on the production and proportions of plasma and milk fat vaccenic acid (VA), conjugated linoleic acid (CLA), and linolenic acid in diary cattle. In experiment 1, the cows consumed 50, 65, and 80% of their feed intake as pasture with the remainder of intake as a barley-based concentrate. The proportion of VA in milk fatty acids increased 12% when pasture intake increased from 50 to 65% of total dry matter intake and VA, CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 14 publications
1
16
0
3
Order By: Relevance
“…This may be related to differences in the nutritional composition of the herbage, which has also been shown to affect the fatty acid composition of milk (Dewhurst et al, 2006). In this respect, lower CLA contents in milk have been observed with more mature pasture, and this effect has been attributed to the declining quality and quantity of the herbage (Lock & Garnsworthy, 2003;Ward et al, 2003). This is in agreement with the present work, in which the lowest CLA values were obtained in late December and January, when the herbage presented the poorest nutritional quality (see Table 2).…”
Section: Cla Content and Compositionmentioning
confidence: 95%
“…This may be related to differences in the nutritional composition of the herbage, which has also been shown to affect the fatty acid composition of milk (Dewhurst et al, 2006). In this respect, lower CLA contents in milk have been observed with more mature pasture, and this effect has been attributed to the declining quality and quantity of the herbage (Lock & Garnsworthy, 2003;Ward et al, 2003). This is in agreement with the present work, in which the lowest CLA values were obtained in late December and January, when the herbage presented the poorest nutritional quality (see Table 2).…”
Section: Cla Content and Compositionmentioning
confidence: 95%
“…La composición de los ácidos grasos (AG) en gramíneas tiene especial importancia por su efecto sobre el perfil lipídico en la carne y la leche de los rumiantes (Dhiman et al 1999;White et al 2001;Ward et al 2003;Loor et al 2003;Shingfield et al 2013). En humanos, la grasa de la leche ha sido relacionada con problemas de salud, especialmente, con enfermedades coronarias, niveles altos de lipoproteínas de baja densidad (LDL) y arteriosclerosis, debido a su contenido alto de ácidos grasos saturados (70 %) y al contenido bajo de ácidos grasos insaturados (30 %) (Jensen 2002).…”
Section: Introductionunclassified
“…In this respect, lower CLA contents in milk have been observed with more mature pasture. This effect has been attributed to the declining quality and quantity of the herbage (Lock & Garnsworthy, 2003;Ward et al, 2003;Avilez et al, 2012). In exp.…”
Section: Cla Content and Compositionmentioning
confidence: 99%
“…For instance, it has been reported that fresh forage (Khanal et al, 2005;Dewhurst et al, 2006;Butler et al, 2008; Conjugated linoleic acid content in milk of Chilean Black Friesian cows under pasture conditions and supplemented with canola seed (Brassica napus) concentrate Rego et al, 2008) and diets supplemented with plant oils, high in linoleic acid Stanton et al, 2003) increase CLA concentration in milk fat. Within the seeds of oilseeds, rapeseed (Brassica napus) has been used in TMR (total mixed ration) diets in dairy cows (Bayourthe et al, 2000, Chouinard et al, 2001Ward et al, 2002;Chichlowski et al, 2005;Chen et al, 2008;Neves et al, 2009;Lerch et al, 2012b). However, the information about its utilization as a supplement under grazing conditions is limited and contradictory (Stanton et al, 1997;Lawless et al, 1998;Fearon et al, 2004;Lerch et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%